Guadalajara de Buga, el espacio publico efectivo como elemento estructurante identitario. (2023)
Colombia has been one of the countries most affected by corruption and violence in Latin America, which has generated high rates of internal migration in the nation, turning people from the countryside to the municipal and urban centers of the cities, overpopulating them and making the public space, housing and other services are totally deficient to meet and serve such a volume of population.